Office hysteroscopy in the management of women with postmenopausal bleeding. (3rd July 2020) - Giampaolino, P.; Della Corte, L.; Di Filippo, C.; Mercorio, A.; Vitale, S. G.; Bifulco, G.
Abstract: Postmenopausal bleeding (PMB) is a relevant aspect for health-care providers in clinical practice: the first objective is to rule out potential gynecological cancer. The purpose of this narrative review is to evaluate the role of office hysteroscopy in the management of PMB. Office hysteroscopy is a minimally invasive procedure allowing direct visualization of uterine pathology without the need for general anesthesia and the use of an operating room, generating cost savings and greater compliance among patients. Here, we focus on major intrauterine diseases (polyps, submucosal myomas, endometrial hyperplasia, and cancer) as causes of PMB. Office hysteroscopy appears to be safe and feasible, and could allow accurate diagnosis of intrauterine pathologies, especially that with a focal growth pattern, otherwise misdiagnosed with blinded procedures. However, studies focusing exclusively on postmenopausal women are still few, so further research, especially randomized controlled trials, is needed.